2014
DOI: 10.1038/pr.2014.172
|View full text |Cite
|
Sign up to set email alerts
|

Dietary proteins and IGF I levels in preterm infants: determinants of growth, body composition, and neurodevelopment

Abstract: IGF I, insulin-like growth factor I; sDs, standard deviation score; WFL, weight-for-length. ↑ = positive correlation; ↓ = negative correlation; → = no correlation; Δ = gain. a Chronological age. b Corrected age. c higher IGF I levels in infants with accelerated previous weight and length gain (a difference of more than 0.67 sDs between two study points).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…Postnatal growth deficits are common among preterm infants (7), and at term-corrected age, preterm infants may show increased body fat proportion, relative to term infants, indicating nutritional and metabolic imbalances (29). These effects may relate to low levels of IGF-1 following preterm birth (24,25,53) that have also been associated with a smaller brain volume at term-corrected age (25) and a higher risk of suboptimal neurodevelopment at 2 yr old (26). Until now, a clinically relevant animal model of preterm birth that allows detailed study of organ development and physiology beyond the immediate postnatal period has not been available.…”
mentioning
confidence: 99%
“…Postnatal growth deficits are common among preterm infants (7), and at term-corrected age, preterm infants may show increased body fat proportion, relative to term infants, indicating nutritional and metabolic imbalances (29). These effects may relate to low levels of IGF-1 following preterm birth (24,25,53) that have also been associated with a smaller brain volume at term-corrected age (25) and a higher risk of suboptimal neurodevelopment at 2 yr old (26). Until now, a clinically relevant animal model of preterm birth that allows detailed study of organ development and physiology beyond the immediate postnatal period has not been available.…”
mentioning
confidence: 99%
“…A recent review pointed out that IGF-1 concentrations correlate differently with growth before and after term-equivalent age in preterm infants (22). Hansen-Pupp et al (24) reported that IGF-1 concentrations correlated positively with weight gain at an early postnatal age in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Van de Lagemaat et al (25) reported that both preceding length and weight growth were positively associated with IGF-1 at term, 3 and 6 months CA. After term age, studies show contradictive results in relation to IGF-1 concentrations and correlations with subsequent growth (22). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations